1981
DOI: 10.1163/156853981x00347
|View full text |Cite
|
Sign up to set email alerts
|

Vocal Recognition of Recorded Lambs Voices By Ewes of Three Breeds of Sheep

Abstract: Vocal recognition of lamb's voices by their dams was investigated in Border Leicester, Jacob and Soay sheep, using recordings of lambs voices which were played to ewes simultaneously with presentation of a moving model lamb when the lambs were 15-20 days and 40-50 days of age. The number of bleats made by the ewes during playback of own and alien lamb voices was recorded and then the number of times a ewe bleated in answer to a lamb's bleats within 2 s of hearing the lamb bleat was counted. At both age groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…This indicates that in a double-choice test situation ewes and lambs are able to discriminate their kin on the basis of acoustic cues (high-pitched bleats in the present study) earlier than what had previously been reported in the literature (Alexander, 1977;Poindron & Carrick, 1976;Searby & Jouventin, 2003;Shillito & Alexander, 1975;Shillito-Walser et al, 1981). There is little doubt that this discrimination in ewes and lambs relies on acoustic cues.…”
Section: Discussion Early Vocal Discrimination Between Ewes and Lambssupporting
confidence: 60%
See 3 more Smart Citations
“…This indicates that in a double-choice test situation ewes and lambs are able to discriminate their kin on the basis of acoustic cues (high-pitched bleats in the present study) earlier than what had previously been reported in the literature (Alexander, 1977;Poindron & Carrick, 1976;Searby & Jouventin, 2003;Shillito & Alexander, 1975;Shillito-Walser et al, 1981). There is little doubt that this discrimination in ewes and lambs relies on acoustic cues.…”
Section: Discussion Early Vocal Discrimination Between Ewes and Lambssupporting
confidence: 60%
“…One possibility is that ewes and lambs learn to recognize the individual acoustic signature of their kin in 24-48 hr, since the existence of such a signature is well established in sheep and it is used at later stages of lactation (Alexander, 1977;Nowak, 1991;Poindron & Carrick, 1976;Searby & Jouventin, 2003;Shillito & Alexander, 1975;Shillito-Walser et al, 1981). Our results may suggest that this is already the case at 12 hr for mothers and at 24 hr for lambs.…”
Section: Possible Mechanisms Involved In the Display Of Early Mutual mentioning
confidence: 71%
See 2 more Smart Citations
“…In addition, if the subject emitted more bleats during the rest of the test (1 min after playback of the third bleat), he was given one additional point. A major weight was given to this variable because, in other studies (Shillito-Walser et al, 1981;Searby and Jouventin, 2003), the bleating rate has been shown to be positively correlated with recognition. (v) Reunion of mother and young during the playback or the following minute of observation, ending with sucking: 1 point.…”
Section: Criteria Of Responsementioning
confidence: 99%